A meta-network approach to an IT organization from the perspective of the least socially integrated actors - Ujwary-Gil, Anna (Zarządzanie strategiczne w dobie cyfrowej gospodarki sieciowej, 2020)
The purpose of the article is to identify people (social actors) least task integrated, least socially connected and with the lowest shared situation awareness. The research premise is to look at the effectiveness of the organization from the perspective of a multimodal meta-network consisting of social actors, knowledge, resources, and tasks. The research methodology is network research, including defining the (organizational) network border and the research population; identification of relationship networks (matrix definitions); organizational network analysis metrics, such as cognitive demand, Simmelian tie, and shared situation awareness; correlating variables using scatter plot. The results indicated actors on the outskirts of the organization’s social network in connection with the professional experience of individual actors, which require in-depth analysis.